SISTEM APLIKASI SKRINING TINGKAT DEHIDRASI MENGUNAKAN METODE CASE BASE REASIONING DAN CERTAINTY FACTOR - Yumarlin MZ (Universitas Janabadra, 2021)
Water is an important nutrient needed by the body. Dehydration is a condition when human body tissue loses fluids abnormally and this is very often underestimated so that sometimes severe dehydration can cause death. However, for now the detection of dehydration is only based on the analysis of the health team with several clinical signs of dehydration. From these problems, it is necessary to have research related to automation systems to detect levels of dehydration that can be used by ordinary people, so as to reduce the number of dehydration sufferers who are not treated because they do not know the symptoms of dehydration from the start.The purpose of this study is to develop a screening application to identify the level of dehydration in the human body that combines CBR (case base reasoning) and CF (certainty factor) methods to achieve higher accuracy values. With this screening application, it is hoped that users can easily and quickly find out the level of dehydration they experience based on the symptoms they feel and also get information about solutions for treatment or treatment that need to be done before coming to the health center or to the doctor.Based on the results of the screening application trial of 15 respondents to identify the level of dehydration in the body, it showed 60.03% stated good with an average overall score of 3.87 for the user interface aspect. The software engineering aspect shows 53.35% states good (agree) with an average overall assessment score of 3.92 which indicates that the screening application system developed and made can be used as a reference to help users or users determine the level of dehydration of the body. Keywords: Dehidrasi, Skrining, Case Base Reasioning, Certainty Factor.